Unilateral cerebellothalamic tract ablation in essential tremor by MRI-guided focused ultrasound. (4th April 2017) - Schreglmann, Sebastian R.; Bauer, Ronald; Hägele-Link, Stefan; Bhatia, Kailash P.; Natchev, Parashkev; Wegener, Nikolas; Lebeda, Anita; Werner, Beat; Martin, Ernst; Kägi, Georg
Abstract : Objective: To report results of a prospective trial of unilateral transcranial MRI-guided focused ultrasound (MRIgFUS) ablation of the cerebellothalamic tract in essential tremor (ET). Methods: This was a prospective, uncontrolled, single-center interventional study. Patients with ET fulfilling criteria for interventional therapy received unilateral ablation of the cerebellothalamic tract (CTT) by MRIgFUS. Motor symptoms, manual dexterity, cognition, and quality of life were assessed before intervention and at 48 hours and 1, 3, and 6 months after intervention. Rating of standardized video recordings was blinded for evaluation time points. Primary outcome was the change in unilateral hand tremor score of the treated hand. Results: Six patients received MRIgFUS ablation of the CTT contralateral to the treated hand. Repeated-measures comparison determined a statistically significant 83% reduction (before vs 6 months after intervention mean ± SD; absolute reduction; 95% confidence interval) in the unilateral treated hand subscore (14.3 ± 4.9 vs 2.5 ± 2.6; 11.8; 8.4–15.2; p < 0.001), while quality of life improved by 52% (50.5 ± 19.4 vs 24.8 ± 11.4; 25.7; 3.5–47.28; p = 0.046). Measures for manual dexterity, attention and coordination, and overall cognition were unchanged. Transient side effects (n = 3) were ipsilateral hand clumsiness and mild gait instability for up to 3 months. Conclusions: Unilateral MRIgFUS lesioning of the CTT was highly efficacious in reducing contralateral hand tremor in ET without affecting fine motor function and dexterity over 6 months of follow-up. Adverse effects were mild and transient. Classification of evidence: This study provides Class IV evidence that for patients with ET, transcranial MRIgFUS ablation of the cerebellothalamic tract improves tremor.